2001
DOI: 10.2337/diabetes.50.12.2752
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Overexpression of Hepatocyte Growth Factor in the β-Cell Markedly Improves Islet Function and Islet Transplant Outcomes in Mice

Abstract: Recent advances in human islet transplantation have highlighted the need for expanding the pool of beta-cells available for transplantation. We have developed three transgenic models in which growth factors (hepatocyte growth factor [HGF], placental lactogen, or parathyroid hormone-related protein) have been targeted to the beta-cell using rat insulin promoter (RIP). Each displays an increase in islet size and islet number, and each displays insulin-mediated hypoglycemia. Of these three models, the RIP-HGF mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
161
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(173 citation statements)
references
References 45 publications
(61 reference statements)
12
161
0
Order By: Relevance
“…Previous studies showed that activin A, betacellulin, hepatocyte growth factor, and VEGF could induce differentiation of pancreatic ␤ cells (29)(30)(31). Culture of E17.5 intestinal epithelial cells with such molecules, however, leads only to very low expression of the insulin gene compared with GLP-1-(1-37) (Fig.…”
Section: Insulin Induction In Intestinal Epithelial Cells Is Due To Amentioning
confidence: 99%
“…Previous studies showed that activin A, betacellulin, hepatocyte growth factor, and VEGF could induce differentiation of pancreatic ␤ cells (29)(30)(31). Culture of E17.5 intestinal epithelial cells with such molecules, however, leads only to very low expression of the insulin gene compared with GLP-1-(1-37) (Fig.…”
Section: Insulin Induction In Intestinal Epithelial Cells Is Due To Amentioning
confidence: 99%
“…that HGF is an insulinotropic factor for adult islet β cells and is able to induce insulin expression in non-β cells [14]. Nicotinamide, in combination with EGF and HGF, resulted in increase in the numbers of islets in in vitro culture of islet progenitor cells [13].…”
Section: Disscussionmentioning
confidence: 98%
“…(Miettinen et al 2000). Hepatocyte Growth Factor (Hgf) also appears important for growth and differentiation of the pancreas (Garcia-Ocana et al 2001) and plays an important role in postnatal insulin secretion via the Hgf receptor (c-met) (Roccisana et al 2005).…”
Section: Pancreatic Growth Endocrine Specification and Islet Cell DImentioning
confidence: 99%